2020
DOI: 10.5603/cj.a2018.0094
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital heart rate reduction and its relation to outcomes of heart failure patients with sinus rhythm: Results from the Polish part of the European Society of Cardiology Heart Failure Pilot and Long-Term Registries

Abstract: In-hospital HR reduction did not influence on the outcomes of HF patients in sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…They concluded that there was a need to wait for hemodynamic stability and a 36-h wash-out period in the sacubitril/ /valsartan group, with 6 h of obligatory observation, may require prolonged hospital stays. However, the median duration of the index hospitalization (5.2 days) was shorter than was shown in a previous analysis from the registry of European Society of Cardiology (median hospital stay was 7 days) [28]. Additionally, there was high discontinuation rate of study drug in both arms and 15% had missing data for the primary endpoint [16].…”
Section: Tion (The Comparison Of Pre-and Post-discharge Initiation Of Lcz696 Therapy In Hfref Patientsmentioning
confidence: 57%
“…They concluded that there was a need to wait for hemodynamic stability and a 36-h wash-out period in the sacubitril/ /valsartan group, with 6 h of obligatory observation, may require prolonged hospital stays. However, the median duration of the index hospitalization (5.2 days) was shorter than was shown in a previous analysis from the registry of European Society of Cardiology (median hospital stay was 7 days) [28]. Additionally, there was high discontinuation rate of study drug in both arms and 15% had missing data for the primary endpoint [16].…”
Section: Tion (The Comparison Of Pre-and Post-discharge Initiation Of Lcz696 Therapy In Hfref Patientsmentioning
confidence: 57%
“…That is, patients presenting with tachycardia and discharged with a controlled HR had better outcomes. In contrast, another study revealed that HR reduction during hospitalization for HF was not associated with better prognosis in patients with sinus rhythm 6 . However, these studies evaluated the HR change at admission and discharge, and no conclusion has been reached as yet.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, another study revealed that HR reduction during hospitalization for HF was not associated with better prognosis in patients with sinus rhythm. 6 However, these studies evaluated the HR change at admission and discharge, and no conclusion has been reached as yet. Several guidelines emphasize the importance of earlier stabilization for haemodynamic abnormalities, 7 and HR often changes dramatically after initial treatment for AHF in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, we have demonstrated that our e-consultation model was associated with improved accessibility to care 11 and reduced cardiovascular mortality and hospital admissions. 3 These facts are particularly relevant in patients with suspected or confirmed AF, since a delayed diagnosis may lead to a poor outcome related to delayed rhythm and rate control 12,13 and, most importantly, a delayed optimisation of OAC. 7 The increased rate of OAC use and the reduction in the elapsed time for clinical assessment of patients with AF after the implementation of our e-consultation program may have influenced our findings.…”
Section: Temporal Trend In Oral Anticoagulation Rate and Elapsed Time...mentioning
confidence: 99%